A comparative study of the viscoelastic constitutive models for frictionless contact interfaces in solids. (March 2015) - Alves, Janete; Peixinho, Nuno; da Silva, Miguel Tavares; Flores, Paulo; Lankarani, Hamid M.
Abstract: The nature of the constitutive contact force law utilized to describe contact–impact events in solid contact interfaces plays a key role in predicting the response of multibody mechanical systems and in the simulation of engineering applications. The goal of this work is to present a comparative study on the most relevant existing viscoelastic contact force models. In the sequel of this process, their fundamental characteristics are examined and their performances evaluated. Models developed based on the Hertz contact theory and augmented with a damping term to accommodate the dissipation of energy during the impact process, which typically is a function of the coefficient of restitution between the contacting solids, are considered in this study. In particular, the identified contact force models are compared in the present study for simple solid impact problems with the sole purpose of comparing the performance of the various models and examining the corresponding system behavior. The outcomes indicate that the prediction of the dynamic behavior of contacting solids strongly depends on the selection of the contact force model. Highlights: A comparative study of viscoelastic contact force models is presented. The dissipated energy is defined in terms of the restitution coefficient. The contact force models are numerically and experimentally analyzed.